Macular Rash, Thrombocytopenia, and Hyperbilirubinemia in a Preterm Infant - Nurin Chatur; Marina Castro; Kin Fan Young Tai (Case Reports in Pediatrics)
Neonatal hyperthyroidism is usually caused by the passage of maternal thyroid receptor antibodies. This relatively rare condition has various manifestations including cholestasis, prematurity, and cardiomegaly. We present a case of a preterm infant with neonatal Graves’ disease who presented with cholestasis, cardiomegaly, and a macularpapular rash that was thought to be suspicious for congenital infection. This case has been reported to illustrate lessons learnt for early identification of a neonate with Graves’ disease in order to expedite treatment.